2019
DOI: 10.1177/2059513119831369
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and genotyping of Acinetobacter baumannii isolated from burn patients by PCR and ERIC-PCR

Abstract: Background: Acinetobacter baumannii is one of the most important agents of hospital infections. Rapid and accurate identification and genotyping of A. baumannii is very important, especially in burn hospitals in order to prevent the spread of related nosocomial infections and to further epidemiological studies. Material and methods: For two months, 82 A. baumannii isolates were collected from burn wound swabs of patients in a major burn hospital in Tehran. A. baumannii isolates were identified by conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 26 publications
1
15
1
Order By: Relevance
“…In term of molecular con rmation, the frequency of A. baumannii was found in the present study was 47 (94%) which is similar to the frequency rate found out by Falah etal., in 2019 whom con rmed 80 (97.56%) of A. baumannii isolates in a total of 82 [2]. While Marathe et al, in 2019 found results which were strongly disagreed with the frequency found in the present study they examined a total of 112 sample and found only 33(30%) con rmed as A. baumannii [10].…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…In term of molecular con rmation, the frequency of A. baumannii was found in the present study was 47 (94%) which is similar to the frequency rate found out by Falah etal., in 2019 whom con rmed 80 (97.56%) of A. baumannii isolates in a total of 82 [2]. While Marathe et al, in 2019 found results which were strongly disagreed with the frequency found in the present study they examined a total of 112 sample and found only 33(30%) con rmed as A. baumannii [10].…”
Section: Discussioncontrasting
confidence: 62%
“…Four species of Acinetobacter including A. calcoaceticus, A. baumannii, A. pittii and A. nosocomialis are similar to each other and it is di cult to distinguish them by phenotypic characteristics. A. baumannii is the commonest species isolated from human clinical specimens, followed by such species as A. luffy, A. pittii, A. nosocomialis, A. haemolyticus and A. johnsonii [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Fallah et al, 82 samples of A. baumannii were isolated from the burn hospital and divided into 14 types of ERIC-PCR patterns, including 11 common types and 3 unique types. In this study, 77 samples were classified into 9 main genotypes [ 24 ]. On the other hand, in the current study 14 different ERIC-types including 7 common types and 7 unique or single types (Strains No.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA from Acinetobacter species was prepared using the boiling method [41]. Quantification of the extracted DNA was determined by spectroscopy at 260 nm.…”
Section: Genotypic Determination Of Carbapenemasesmentioning
confidence: 99%